Child Marriage And Zina In Indonesian Legislation In Islamic Law - Djubaedah, Neng (Jurnal Hukum & Pembangunan, 2019)
Article 7 paragraph (1) of Law No. 1 Year 1974 on Marriage determines marriage permitted if the man is 19 years old and female 16 years old. The age limit of marriage for 16-year-old women is considered an early age and is a problem. Child marriage in this paper is a marriage performed by men and women under the age of 18 years. It is able to cause divorce and obstruction of education. In addition to article 7 paragraph (1), child marriage is also due to pregnancy due to free sex (zina) of teenagers. According to Islamic Law, zina is an out-of-wedlock marriage committed deliberately and consciously by man and woman with their individual willingness, likes, without coercion. How is the protection of Article 7 paragraph (1) on child marriage and women under18 years old who commit zina in terms of Islamic Law? The method of research is normative-juridical and descriptive-qualitative, apply the theory of maqashid al-shari’a and neo receptio a contrario theory.